Maxillary odontogenic myxoma presenting mainly on nasal manifestation: a unique CT appearance of ‘floating’ tooth - Juhari, Najlaa Raihana; Wee, Chong Aun (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
An odontogenic myxoma is a benign odontogenic tumor with locally aggressive behavior. It is relatively rare in the oral cavity. The diagnosis poses a challenge because its features overlap with those of other benign and malignant neoplasms. We present an unusual case of odontogenic myxoma with involvement of the maxilla extending to the maxillary sinus in a 17-year-old lady. A unique computed tomography (CT) appearance revealed a well circumscribed lytic lesion arising from the left maxilla causing expansion and thinning of the maxillary cortex. There is a discernible tooth with adjacent amorphous calcification in a round formation noted within the lesion. Biopsy revealed an odontogenic myxoma. The patient however did not undergo surgical excision as was not consented at the time of this write ups. This paper highlights the unique radiographic appearance of the pathology that has not been reported so far as well as to discuss its clinical significance.